Antioxidant Activities, Total Phenolic Compound And Pigment Contents of Tropical Sargassum sp. Extract, Macerated In Different Solvents Polarity - Jelita Rahma Hidayati; Ervia Yudiati; Delianis Pringgenies; Zaenal Arifin; Diah Tri OktaviyantI (Jurnal Kelautan Tropis, 2019)
Exposure of sunlight lead tropical Sargassum sp. to maintain their growth and moreover to bring up their secondary metabollite for life struggling. Sargassum sp. has bioactive compounds that has a potential antioxidant acitivity such as phenolic compounds as well as chlorophyll and carotenoids. This research was conducted to determine antioxidant activities, phenolic compound and pigmens of Sargassum sp. with different solvent that have different polarities. Sample was macerate with n-heksana, ethyl acetate, methanol and aquadest. All the parameters were done spectrophotometrically. IC50 was used to determine the antioxidant activity by antiradical scavenging activity using DPPH (515 nm). Total phenolic compound were tested by Folin-Ciocalteu solution  and used gallic acid as standard (725 nm). The chlorophylls a content were measured at wavelength 662 nm and 645 nm and carotenoids were measured at wavelength 470 nm. The results showed best IC50 is achieved by aquadest extract (72.95 ±0.22 ppm). The highest Total phenolic compound is achieved by ethyl acetat extract (120.29 ±0,404 mg GAE/g sample). The highest chlorophyll a content is achieved by ethyl acetat extract (18.23 ± 0,049 mg/g sample) and the highest carotenoid content is achieved by ethyl acetat extract extract (60.65 ±0,008  µmol/g sample). It can be concluded that aquadest extract can be categorized as the strong antioxidant and antiradical activity, ethyl acetat as a medium antioxidant activity. The simple and save methods of aquadest extract promising that Sargassum  sp. frorn Indonesia is a good candidate compoud for nutraceutical and cosmeceutical approach.